Cognitive variability in adults with ADHD and AS: Disentangling the roles of executive functions and social cognition - González Gadea, María Luz (2013)
Attention-deficit/hyperactivity disorder (ADHD) and Asperger's Syndrome (AS) share a heterogeneous cognitive profile. Studies assessing executive functions (EF) and social cognition in both groups have found preserved and impaired performances. These inconsistent findings would be partially explained by the cognitive variability reported in these disorders. First, the present study explored the inter-individual variability in EF and social cognition in both patient groups. Second, we compared differential characteristics and commonalities in the cognitive profiles of EF and social cognition between ADHD, AS and control adults. We assessed 22 patients with ADHD, 23 adults with AS and 21 matched typically developing subjects using different measures of EF (working memory, cognitive flexibility and multitasking) and social cognition (theory of mind and decision-making). Group comparisons and multiple case series analyses (MCSA) were conducted. The between-group comparisons showed an EF deficit in working memory in ADHD and a theory of mind (ToM) impairment in AS. The MCSA evidenced that, compared to controls, ADHD patients had a higher inter-individual variability in EF, while individuals with AS had a more heterogeneous profile in social cognition tasks compared to both groups. Finally, the AS and ADHD groups presented higher task-related variability compared to controls and shared a common heterogeneous profile in EF. This is the first study to compare variability in EF and social cognition profiles of ADHD and AS. We propose that heterogeneity in EF performance is a link between ADHD and AS which may explain the overlap of symptomatology between both diagnoses. In addition, patients with AS seem to show a unique heterogeneous profile in ToM which may explain the low probability of finding AS symptoms in patients with ADHD.